TEKNIK ABDOMINAL LIFTING MENCEGAH NYERI PERSALINAN KALA I DI PMB KABUPATEN MALANG - Raden Maria Veronika Widiatrilupi; Rosyidah Alfitri (JOMIS (Journal of Midwifery Science), 2024)
One of the non-pharmacological measures that can reduce labor pain is the provision of abdominal lifting. Abdominal lifting is a technique of giving opposite strokes towards the top of the abdomen without applying pressure down the back which aims to reduce pressure on the lower back of the laboring mother which is applied from the beginning of labor to the next stage using the gravity technique. The purpose of this study was to determine the effectiveness of abdominal lifting techniques to prevent labor pain. Thus, the lack of references regarding this technique supports the implementation of this study. This type of research is a quasi experiment with pre-post design. The population consisted of 50 respondents with a sample size of 36 respondents who were divided into treatment groups and control groups. Giving abdominal lifting techniques is done every time there is a contraction given for 15 minutes with the patient lying down. This research was conducted at PMB Yuni Ermawati - Pagelaran in March - June 2023. The measuring instrument used is the numeric pain rating scale (NPRS) which is measured at opening 3 and opening 8. By using a diagrammatic data presentation on the pain intensity of the two groups and analyzing the data in analyzing the group differences, the P-value of the mann-whitney test shows the results of the study after giving the abdominal lifting technique 0.00 <0.05 on the difference between the treatment group and the control group. The conclusion of this study is that the provision of abdominal lifting techniques can prevent labor pain in the first stage. Further research is recommended to conduct comparisons between pharmacological techniques with research designs on each opening of labor.